2019
DOI: 10.21432/cjlt27813
|View full text |Cite
|
Sign up to set email alerts
|

Les déterminants technologiques de la persévérance des étudiants dans les cours à distance de niveau collégial : Les modalités de cours jouent-elles un rôle?

Abstract: L’objectif de cette étude est d’identifier et d’analyser les déterminants technologiques de la persévérance dans les cours à distance de niveau collégial (n=61), issus du modèle Unified theory of acceptance and use of technology (UTAUT). Les résultats des analyses par équations structurelles (Partial Least Square) indiquent que parmi ces derniers déterminants, seulement les conditions facilitantes ont un impact significatif et positif sur l’intention comportementale d’utiliser les technologies des cours à dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 36 publications
2
11
0
Order By: Relevance
“…This model is selected here because it includes technological factors that are different and complementary to other explicative models for persistence in online courses. Some factors of this model, partially present in the earlier models, have been found to be significant in explaining persistence in online courses: performance expectancy and effort expectancy (Joo et al 2011), social influence (Kember 1989;Park 2007;Rovai 2003) and facilitating conditions (Lakhal, 2019). According to Venkatesh et al (2003), the UTAUT model should be enriched by additional factors such as individual constructs.…”
Section: Problemmentioning
confidence: 95%
See 3 more Smart Citations
“…This model is selected here because it includes technological factors that are different and complementary to other explicative models for persistence in online courses. Some factors of this model, partially present in the earlier models, have been found to be significant in explaining persistence in online courses: performance expectancy and effort expectancy (Joo et al 2011), social influence (Kember 1989;Park 2007;Rovai 2003) and facilitating conditions (Lakhal, 2019). According to Venkatesh et al (2003), the UTAUT model should be enriched by additional factors such as individual constructs.…”
Section: Problemmentioning
confidence: 95%
“…Yet in these models, technological factors are little, or not at all, taken into account. Digital technologies play a significant role in online courses, notably in regards to their implementation, and these technological factors may play an important role in the decision to persist in or drop out from online courses (Hachey et al 2014;Lakhal and Bazinet 2015;Lakhal 2019). Indeed, some studies identified by Lakhal and Bazinet (2015) indicate that the use of technologies (prior experience with the technologies, the variety of technology used, the use of social networks, etc.)…”
Section: Problemmentioning
confidence: 99%
See 2 more Smart Citations
“…Thanks to ICT, these delivery modes offer advantages both to students and to postsecondary institutions. On the one hand, depending on their design, blended and online courses have the potential to meet the demands of students who desire flexible course schedules, such as adult students, because of family and/or work responsibilities (Lakhal, 2019). They also give students better access to higher education, especially in large countries such as Canada where distances can be quite significant between students' homes and their colleges or universities (Lakhal et al, 2020), and they allow both synchronous and asynchronous contacts between students and with the instructor, even if students would not need to travel as much to attend face-to-face sessions (Cidral et al, 2018).…”
Section: A Continuum Of Blended and Online Learningmentioning
confidence: 99%